Potencial de aplicação de nanopartículas de prata produzidas pela síntese verde utilizando os fungos endofíticos Fusarium spp. e Penicillium spp. - Garcia, Laisa Adriana de Paula Luizon (Universidade Federal de São Carlos, 2024)
In the post-pandemic scenario, where concern about ways to protect against bacteria and viruses has increased, the application of silver nanoparticles (AgNPs) in fabrics stands out as an approach less susceptible to microbial resistance. These materials can be incorporated into clothing, masks, and personal protective equipment (PPE), providing additional barriers against pathogen infections and enhancing the quality and lifespan of fabrics. In the context of sustainable production, the green synthesis of AgNPs represents a sustainable and efficient alternative for producing materials with antimicrobial properties. This study investigated the potential for fabricating AgNPs using fermentation broths of the endophytic fungi Fusarium sp. and Penicillium sp. isolated from the plant Polygala paniculata, native to the Atlantic Forest. The green synthesis conducted with the broth of Fusarium sp. produced AgNPs (NPs-F) with an average diameter of 59 nm, while the AgNPs produced by the Penicillium sp. broth (NPs-P) had an average diameter of 85 nm. Regarding antimicrobial activity, NPs-F showed greater bactericidal and antibiofilm potential, requiring a much higher concentration of NPs-P to achieve the same results observed with NPs-F. It was also noted that the fermentation broth of Penicillium sp. demonstrated much higher synthesis efficiency, producing approximately 2,54 × 1010 particles/mL, double the amount of AgNPs produced by the Fusarium sp. broth. Despite this, the efficiency of green synthesis remains a challenge to be addressed, with relatively low conversions of AgNO3 into AgNPs, requiring optimizations to enable its production on an industrial scale
Potential application of silver nanoparticles produced by green synthesis utilizind the endophytes fungi Fusarium spp. and Penicillium spp.
Keywords: Endófitos; Síntese verde; Nanopartículas de prata; Antimicrobianos; Fungos; Endophytes; Green synthesis; Silver nanoparticles; Antimicrobials; Fungi; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::BIOLOGIA E FISIOLOGIA DOS MICROORGANISMOS::BACTEROLOGIA